2007
DOI: 10.1021/ja070855c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Reactions of 20 π-Electron β-Tetrakis(trifluoromethyl)-meso-tetraphenylporphyrins

Abstract: Porphyrin and their analogues usually have a stable aromatic (4n + 2) π-electron system. Porphyrin itself shows aromatic behavior with an 18 π-electron main conjugation pathway in the molecule and has been intensively investigated. 1 However, porphyrin derivatives with 4n π-electron delocation pathways have been little explored owing to their synthetic difficulty, 2,3 and the majority of them are expanded porphyrins 3 because the difference between resonance stabilization energies of 4n and (4n + 2) π-electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
94
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(96 citation statements)
references
References 19 publications
2
94
0
Order By: Relevance
“…In the pioneering studies on the structure-property relationship of core-modified isophlorins, Vogel and co-workers exemplified conformation-induced loss of paratropism in a saddle-shaped tetra-N-methyl β-octaethylporphyrin (N 4 -isophlorin) [15]. Chen's β-tetrakis(trifluoromethyl)-meso-tetraphenylporphyrin also adopts a highly distorted saddle conformation and shows almost complete conformation-induced loss of paratropicity in the 20π isophlorin system [16]. By contrast, Setsune's N 21 ,N 22 -bridged N 4 -isophlorins are not highly deviated from planarity and exhibit paratropic ring current effects in the 1 H NMR spectra [17].…”
Section: Crystal Structuresmentioning
confidence: 99%
“…In the pioneering studies on the structure-property relationship of core-modified isophlorins, Vogel and co-workers exemplified conformation-induced loss of paratropism in a saddle-shaped tetra-N-methyl β-octaethylporphyrin (N 4 -isophlorin) [15]. Chen's β-tetrakis(trifluoromethyl)-meso-tetraphenylporphyrin also adopts a highly distorted saddle conformation and shows almost complete conformation-induced loss of paratropicity in the 20π isophlorin system [16]. By contrast, Setsune's N 21 ,N 22 -bridged N 4 -isophlorins are not highly deviated from planarity and exhibit paratropic ring current effects in the 1 H NMR spectra [17].…”
Section: Crystal Structuresmentioning
confidence: 99%
“…The bond lengths for 16 p-electron [50,56,58] and 18 p-electron [46,[51][52][53] porphyrin rings in comparison with those of the Pt-complex obtained from X-ray analysis are listed in Table 4. From this table, it is found that there is much similarity in the values of bond distances of 18 p-electron rings and the Pt-complex reported here.…”
Section: X-ray Crystal Structure Of [(Tmp)pt(oh) 2 ]á2metachlorobenzomentioning
confidence: 99%
“…The macrocycle can have a versatile character; the most stable and abundant oxidation state of the macrocycle is the normal aromatic 18 p-electron ring in which the macrocycle has a À2 oxidation state. Under reducing conditions, monoanion radical 19 p-electron and anti-aromatic 20 p-electron dianion systems have been recognized [50][51][52][53]. In the oxidative environment of the enzyme, porphyrin p-cation radical with 17 p-electron system has been proposed [22,54,55].…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14] As a consequence, a majority of studies on [4n]p porphyrinoids have dealt with expanded porphyrins, because the difference in resonance stabilization energies between [4n]p and [4n+2]p electronic systems decreases for larger values of n. [5,15] In this regard, the isolation and stability of [4n]p porphyrinoids are the essential requirements for the reliable photophysical characterization. Chen et al [16] reported in 2007 that trifluoromethyl groups on pyrrole rings give rise to relatively air-stable [20]p porphyrin. After this work, Hayashi et al [17] also reported the successful synthesis and isolation of air-stable [20]p b-tetrakis(trifluoromethyl) porphycene ( [20]CF 3 Pc) through two-electron reduction and two protonation processes of [18]p b-tetrakis (trifluoromethyl)porphycene ([18]CF 3 Pc), which seems to be an analogue of etioporphycene ( [18]EtioPc) (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%